Struktur Anatomi Daun, Kantung dan Sulur Nepenthes gracilis Korth. yang Tumbuh di Area Intensitas Cahaya Berbeda - Riza Linda, Niken Paluvi, Mukarlina (Universitas Tanjungpura, 2015)
Sunlight is one factor that plays a major role in the process of the plant physiology. Plants will go through a variety of morphological and anatomical changes in order to be able to adapt to the environment with varying light intensity. This research aims to know the anatomical structure of leaves, foliage and Nepenthes gracilis Korth. tendrils which grow in areas with different light intensity. The research was conducted from May 2014 to September 2014. The paraffin method is used inmaking preparations of transverse incision of leaves, foliage, and N. gracilis tendrils. The results of the study on the transverse incision of the leaves, foliage and tendrils growing at different light intensity indicated a difference in the thickness of the epidermis, stomata number, thickness of cortical cell layers and size of the vessel. N. gracilis that were grown in the shaded area had thinner epidermal thickness of leaf which was 3.24 ± 0,48μm than those grown in an open area which was 6.59 ± 1,35μm. The number of stomata grown in a shaded area was fewer i.e. 44 compared to that grown in the open area which was 84. The thickness of the cortical cell layers of tendrils grown in the shaded area was thinner which was 155.30 ± 2.79 μm than those grown in an open area that was 176, 49 ± 4,23μm and the size of the vessel on the leaves and tendrils grown in the shaded area was smaller than those grown in an open area.